2008
DOI: 10.1149/1.3055409
|View full text |Cite
|
Sign up to set email alerts
|

Temperature Gradient Induced Water Transport in Polymer Electrolyte Fuel Cells

Abstract: The objective of this work is to investigate water transport of polymer electrolyte fuel cell (PEFC) materials subjected to a temperature gradient. Direct thermo-osmotic experiments on different polymer membrane types (non-reinforced Nafion ® , reinforced A, and reinforced B membrane) were performed using an in-house fuel cell fixture with a parallel flow field. Thermoosmotic flow was observed in all membranes, and the water flow direction (in the membrane only) was determined to always flow from the cold side… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
14
0

Year Published

2008
2008
2021
2021

Publication Types

Select...
4
2

Relationship

1
5

Authors

Journals

citations
Cited by 7 publications
(14 citation statements)
references
References 22 publications
0
14
0
Order By: Relevance
“…where D TO is thermo-osmotic diffusivity in the membrane and is a function of temperature. 26,27 3. Energy conservation in the porous media…”
Section: Mass Conservation In the Membranementioning
confidence: 99%
See 4 more Smart Citations
“…where D TO is thermo-osmotic diffusivity in the membrane and is a function of temperature. 26,27 3. Energy conservation in the porous media…”
Section: Mass Conservation In the Membranementioning
confidence: 99%
“…Kim and Mench 26,27 observed that thermo-osmotic flux of water in three different commercial perfluorinated PEMs flows from the cold to hot side of the membrane and that reinforcement did not affect the flow direction. The net flux, however, was altered by the reinforcement structure.…”
mentioning
confidence: 99%
See 3 more Smart Citations